Control of Mechanotransduction by Molecular Clutch Dynamics. Issue 5 (May 2018) - Elosegui-Artola, Alberto; Trepat, Xavier; Roca-Cusachs, Pere
Abstract : The linkage of cells to their microenvironment is mediated by a series of bonds that dynamically engage and disengage, in what has been conceptualized as the molecular clutch model. Whereas this model has long been employed to describe actin cytoskeleton and cell migration dynamics, it has recently been proposed to also explain mechanotransduction (i.e., the process by which cells convert mechanical signals from their environment into biochemical signals). Here we review the current understanding on how cell dynamics and mechanotransduction are driven by molecular clutch dynamics and its master regulator, the force loading rate. Throughout this Review, we place a specific emphasis on the quantitative prediction of cell response enabled by combined experimental and theoretical approaches. Highlights: By considering the molecular and mechanical properties of actin filaments, myosin motors, adaptor proteins, and integrins/cadherins, the molecular clutch model can quantitatively predict cell response to internal and external mechanical factors. These factors include cell contractility, matrix rigidity, and the density, nature, and distribution of matrix ligands, and affect cell response largely by controlling the rate of force loading in specific molecules. Due to its dynamic nature, clutch-mediated mechanosensing requires force application to at least two molecular mechanosensors in series, with differential response to force. The type of cell responses involved so far in clutch-mediated mechanosensing include cytoskeletal dynamics, the growth of cell adhesions, the nuclear localization of transcriptional regulators, and cell migration.